Variable Selection Strategy Using Random Forests Algorithm to Identify the Effects of Environmental Factors on Health, Modeling from a GIS Multidimensional Dataset - Bourrelly, Stéphane (Journal of Environmental Accounting and Management, 2026)
This paper proposes the method: MyVsurfGeo (MVG), designed to assess the adverse effects of living environments; of key interest in France’s cancer plans. Increased access to numerous databases enables modeling physicochemical, sanitary and socio-economic features at territorial scale, from Geographic Information Systems (GIS). However, GIS are not suited for characterizing relationships in existing high multidimensional datasets. Especially, when incorporating qualitative and quantitative indicators, with different accuracy levels. A recent strategy of variable selection using Random Forests provides the power to overcome this drawback. MVG1 method transposes this strategy into spatial analysis. It is applied to secondary tumors (TUM2) developed during a childhood leukemia remission. Results highlight health determinants and contributory factors that explain TUM2 incidences. The significance of MVG and its findings are discussed. The expected medical and political contributions are described.